FACTORS ASSOCIATED WITH THE DEVELOPMENT OF SECONDARY HYPERPARATHYROIDISM IN PATIENTS WITH TYPE 1 DIABETES MELLITUS WITH DIABETIC NEPHROPATHY - Ye. A. Khantakova (Бюллетень сибирской медицины, 2014)
Objective. To identify factors associated with the development of secondary hyperparathyroidism in patients with type 1 diabetes mellitus with diabetic nephropathy.Materials and methods. One hundred and one patients (males) with type 1 diabetes mellitus with diabetic nephropathy who were treated in endocrinology department of the Regional clinical hospital were examined. For the study of calcium and phosphorus metabolism in patients with type 1 diabetes mellitus, we investigated the following parameters in the blood plasma: level of intact parathyroid hormone, total calcium, ionized calcium, serum phosphorus.Results. The study showed that in patients with type 1 diabetes mellitus with diabetic nephropathy factors associated with the development of secondary hyperparathyroidism are: the age above 30 years old, the duration of diabetes for more than 15 years, reduction of glomerular filtration rate of less than70 ml/min/1,73 m2 and the development of anemia. Factor associated with the reduction of secondaryhyperparathyroidism is the level of glycated hemoglobin of more than 8%.Conclusion. Thus, patients with type 1 diabetes mellitus with diabetic nephropathy represent a group of increased risk for development of violations of calcium and phosphorus metabolism. Analysis of the factors associated with the occurrence of secondary hyperparathyroidism in diabetic nephropathy allowed to identify a group of high risk of development of this pathology.